Stiftung Ludwig Köln 1976 : Ludwig Donation. - Stiftung Ludwig, Köln (Köln : Städt Köln, 1976)
Klein, Yves ; Kosuth, Joseph ; Kusama, Yayoi ; Le Va, Barry ; LeWitt, Sol ; Lichtenstein, Roy ; Lindner, Richard ; Louis, Morris ; Mack, Heinz ; Manzoni, Piero ; Paolozzi, Eduardo ; Penck, A.R. ; Picasso, Pablo ; Twombly, Cy ; Uecker, Günther ; Ursula ; Wesselmann, Tom ; etc.
boek